2014
DOI: 10.1645/13-371.1
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Profiles for Western Fence Lizards,Sceloporus occidentalis, Naturally Infected by the Malaria ParasitePlasmodium mexicanum

Abstract: Plasmodium mexicanum is a malaria parasite that naturally infects the western fence lizard, Sceloporus occidentalis , in northern California. We set out to determine whether lizards naturally infected with this malaria parasite have different leukocyte profiles, indicating an immune response to infection. We used 29 naturally infected western fence lizards paired with uninfected lizards based on sex, snout-to-vent length, tail status, and the presence-absence of ectoparasites such as ticks and mites, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…We had predicted that eosinophils would be elevated in infected anoles because they are responsible for protection against protozoal parasites (Strik et al 2007). Similar to Motz et al (2014), we found no such effect, which may mean that eosinophils are not as important in protozoal immunological responses in reptiles as previously assumed. Alternatively, Plasmodium may not elicit an eosinophil response even if other protozoans do, or the low parasitemia of P. floridense in Florida anoles (Perkins et al 2009, Doan et al 2019 may not be enough to cause a detectable eosinophil response.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We had predicted that eosinophils would be elevated in infected anoles because they are responsible for protection against protozoal parasites (Strik et al 2007). Similar to Motz et al (2014), we found no such effect, which may mean that eosinophils are not as important in protozoal immunological responses in reptiles as previously assumed. Alternatively, Plasmodium may not elicit an eosinophil response even if other protozoans do, or the low parasitemia of P. floridense in Florida anoles (Perkins et al 2009, Doan et al 2019 may not be enough to cause a detectable eosinophil response.…”
Section: Discussionsupporting
confidence: 76%
“…In humans, eosinophil levels change dramatically over the course of infection (Kurtzhals et al 1998) and vary with severity of infection (Saidu et al 2015). Motz et al (2014) found no significant difference between Sceloporus occidentalis infected with Plasmodium mexicanum versus uninfected. To our knowledge, no studies have assessed the relationship of eosinophil levels and Plasmodium infection in anoles.…”
Section: Introductionmentioning
confidence: 65%
“…Here, we used the correlation between these metrics to provide an initial distinction between two alternative possibilities based on work in other squamates. As many parasites illicit an immune response (i.e., inflammation, Murphy, 2012), parasite burden could be positively correlated with humoral and cellular immunocompetence (i.e., a responsive immune effect, Motz, Lewis, & Vardo‐Zalik, 2014; Spence, Durso, Smith, Skinner, & French, 2017). Alternatively, animals with comparatively lower immunocompetence may be more susceptible to parasitism, and thus might have a higher parasite burden (i.e., a causative immune effect).…”
Section: Introductionmentioning
confidence: 99%
“…Malaria parasites have been described in a wide range of hosts in the Americas, including humans [1], monkeys [2], free-living birds [3], reptiles [4] and rodents [5]. Among non-primate mammals, Plasmodium species had been thought to be limited to the Old World.…”
Section: Introductionmentioning
confidence: 99%